Changes in Glutathione Content in Liver Diseases: An Update - Mariapia Vairetti; Laura Giuseppina Di Pasqua; Marta Cagna; Plinio Richelmi; Andrea Ferrigno; Clarissa Berardo (MDPI AG, 2021)
Glutathione (GSH), a tripeptide particularly concentrated in the liver, is the most important thiol reducing agent involved in the modulation of redox processes. It has also been demonstrated that GSH cannot be considered only as a mere free radical scavenger but that it takes part in the network governing the choice between survival, necrosis and apoptosis as well as in altering the function of signal transduction and transcription factor molecules. The purpose of the present review is to provide an overview on the molecular biology of the GSH system; therefore, GSH synthesis, metabolism and regulation will be reviewed. The multiple GSH functions will be described, as well as the importance of GSH compartmentalization into distinct subcellular pools and inter-organ transfer. Furthermore, we will highlight the close relationship existing between GSH content and the pathogenesis of liver disease, such as non-alcoholic fatty liver disease (NAFLD), alcoholic liver disease (ALD), chronic cholestatic injury, ischemia/reperfusion damage, hepatitis C virus (HCV), hepatitis B virus (HBV) and hepatocellular carcinoma. Finally, the potential therapeutic benefits of GSH and GSH-related medications, will be described for each liver disorder taken into account.